(untitled) (Research, Society and Development, 2021)
The aim of this study was to analyze the contribution of realistic simulation of undergraduate nursing education. This is an integrative review study, with a qualitative approach, with data collected through the search for articles attached in the databases referring to the Virtual Health Library and Latin American and Caribbean Literature in Health Sciences. The combination of descriptors in the research were simulation or simulation and nursing training, and the search period was carried out from January to March 2020. The total bibliographic material of this review was 34 articles. Most of the articles are of a methodological nature, and a research method with a pre- and post-test evaluation tool with practice. The main advantages cited by the journals in relation to the use of realistic simulation were: to facilitate knowledge; self-confidence and precision; approximation of reality and clinical reasoning. This study demonstrated that realistic nursing simulation is becoming a key and innovative learning tool. It is a tool capable of promoting the absorption of knowledge with the development of clinical reasoning, safety and precision in skills.